Brodalumab: A new way to inhibit IL‐17 in psoriasis. Issue 3 (27th April 2020) - Facheris, Paola; Valenti, Mario; Pavia, Giulia; Guanziroli, Elena; Narcisi, Alessandra; Borroni, Riccardo G.; Costanzo, Antonio
Abstract: Psoriasis is a chronic inflammatory disease that affects 2% to 4% of the population; about 20% of the patients present a moderate‐to‐severe form. The IL‐23/Th17/IL‐17 molecular axis is considered crucial in the pathogenesis of psoriasis and IL‐17 is fundamental in the maintenance of the immune and inflammatory alterations causing psoriasis. Expression of IL‐17A, IL‐17F, and IL‐17C is strongly increased in psoriatic plaques. Effective therapy leads to restoration of the expression of a wide range of genes (including effector cytokines and chemokines downstream of IL‐17) to near normal levels. Brodalumab is the first biologic drug targeting specifically the subunit A of the IL‐17 receptor (IL‐17RA) and thus inhibiting not only IL‐17A but also other members of the IL‐17 family. Brodalumab is very effective and safe in treating moderate‐to severe psoriasis.